Advancing aerobic exercise training intensity prescription in health and disease beyond standard recommendations: a call to action - Hansen, D.; Cipriano Junior, G.; Milani, J. G. P. O.; Milani, M.; Gojevic, T.; Machado, F. V. C.; Kambic, T.; Eijsvogels, T. M. H.; Bonifazi, M.; Dendale, P.; D`Ascenzi, F. (Sports Medicine, 2025)
Guidelines for aerobic exercise training (AET) often recommend training intensities on the basis of a percentage of peak effort (e.g. %peak heart rate [%HRpeak], %peak oxygen uptake [%VO2peak]). However, such an approach could be associated with a higher inter-individual variability in acutely induced physiological responses (e.g. blood lactate, HR, VO2) when compared with threshold-based prescription (i.e. ventilatory threshold [VT] or lactate threshold [LT]). Therefore, we performed a literature review to compare the acute physiological impact of AET prescription based on fraction of the peak effort versus threshold-based exercise prescription (VTs and LTs), and how these prescription options may influence the efficacy of exercise intervention in healthy subjects and patients with cardiovascular risk or disease. Data from cross-sectional studies (15 studies; 5312 participants) indeed reveal a greater inter-individual variance in acute physiological responses to a single exercise (e.g. HR, VO2, blood lactate) when exercising at the same %HRpeak or % VO2peak compared with exercising at (a fraction of) VT or LT. Data from randomised exercise intervention studies (3 studies; 135 participants) and a meta-analysis (1544 individuals from 42 studies) show that aerobic exercise prescription based on the percentage of peak effort leads to smaller improvements in VO2peak and metabolic health when compared with aerobic exercise prescription based on the VTs or LT. These collective findings suggest that threshold-based AET intensity prescription elicit more homogeneous acute physiological responses, and greater VO2peak improvements. Hence, it is time to move past standard recommendations and implement a threshold-based approach when prescribing the AET intensity.